Application of a novel ranking approach in QSPR-QSAR - Duchowicz, Pablo Román (2006)
In this study we present a simple algorithm based on the Partial Order Ranking (POR) technique which allows to rank a series of compounds according to their molecular descriptor values. A training set composed of 82 normal boiling points for structurally diverse organic compounds is analyzed by considering a pool of 1202 molecular descriptors obtained from the Dragon 5 software and two “flexible” type of variables. The predictive performance of the proposed approach is assessed by means of a test set of 82 “unknown” structurally related molecules.